Pharmacokinetics of Mycophenolate Mofetil and Development of Limited Sampling Strategy in Early Kidney Transplant Recipients - Zhang, Jun; Sun, Zhi; Zhu, Zhenfeng; Yang, Jing; Kang, Jian; Feng, Guiwen; Zhou, Lin; Zuo, Lihua; Luo, Yonggang; Zhang, Xiaojian (Frontiers in Pharmacology, 2018)
The mycophenolate mofetil (MMF) dose management for optimization of post-transplant treatment especially the early postoperative phase has been well recognized. MMF is a pro-drug of mycophenolic acid (MPA) and is widely used in Chinese renal transplant patients. Until now, the pharmacokinetic (PK) characteristics and model for the area under the concentration–time curve for the 12-hour (h) of exposure (AUC0-12h) of MPA (MPA-AUC0-12h) estimation were lacking for the new formulation of MMF dispersible tablet in renal transplant patients. The aims of the study were to investigate the PK characteristics of MMF dispersible tablet by detecting the active metabolite of MPA and to establish an accuracy and precision equation for calculating MPA-AUC0-12h by limited sampling strategy (LSS) in Chinese kidney transplant patients. A total of 60 postoperative kidney transplant recipients were given a multiple-dose of MMF dispersible tablet twice daily combination with tacrolimus (Tac) and steroids. On the fifth day post-transplantation, blood specimens were collected before drug administration and up to 12 h after MMF dispersible tablet administration. Non-compartmental PK analysis was used to determine the data obtained from individual patients. Multivariate stepwise regression analysis was used to develop models for predicting MPA-AUC0-12h. The 3- and 4-point sampling models using 2h, 4h, 8h and 1h, 2h, 4h and 8h, respectively, allowed accurate estimation of MPA-AUC0-12h. PK parameters of MMF dispersible tablet were obtained and the 4-point LSS is the best model for accurate and precise estimation of MPA-AUC0-12h.